Influence of Electricity Consumption of Industrial and Business, Electricity Price, Inflation and Interest Rate on GDP and Investments in Indonesia - Adi, Tri Wahyu; Prabowo, Eri; Prasadjaningsih, Oetami (International Journal of Energy Economics and Policy, 2022)
This study aims to explore the influence of electricity consumption, electricity price, inflation and interest rate on GDP and investments in Indonesia in the period 2001-2018. This paper is explanatory research. A Generalized Structured Component Analysis was a component-based approach to Structural Equation Modelling has used as a research model. The empirical analysis uses time-series data of GDP, Electricity Consumption, Electricity Price, Inflation Rate, Interest Rate, Investments and GDP in Indonesia in the period 2001-2018. The findings of this study are electricity consumption has a significant positive effect on GDP and electricity price. Electricity price has an insignificant positive effect on electricity consumption and investment. GDP has a significant positive effect on electricity consumption but insignificant on investment and inflation. Investment has an insignificant negative effect on electricity consumption and inflation. Inflation has a significant positive effect on the interest rate, vice versa, but is insignificant to electricity consumption. The interest rate has an insignificant positive effect on investment. The Originality of this study, namely previous studies focused more on the relationships and causality between Electricity Consumption, FDI, GDP, while in this study the emphasis is more on predictions between latent variables using the GSCA. In previous studies using total electricity consumption, in this study, the latent variable of electricity consumption is formed by industry electricity consumption and business electricity consumption which is productive consumption in increasing GDP. This study uses a multi-variate study consisting of Electricity Consumption of Industrial and Business, Electricity Price, Investment, GDP variables, and adding Inflation Rate and Interest Rate that represent macro-economic conditions in the research model.